Frequency of recording and methods of estimation for selection on milk production - Ledic, Ivan Luz; Sobrinho, Evaristo Bianchini; Tupy, Oscar (Pesquisa Agropecuaria Brasileira, 1991)
Three milk-recording methods were compared using 1085 lactations from weekly controls, 1084 from biweekly, 1036 from monthly and 630 from bimonthly. The estimates of genetic parameters and the ranking of bulls were not much affected by the methods used for estimating total milk yield using weekly, biweekly and monthly frequency, anabling the choice among them to be made on basis of practical consideration. In view of the above results, bimonthly yield control is not recommended, because the genetic parameters estimated were null, and bull evaluation was greatly altered. The correlations between partial and total milk yield demonstrated that the latter may be estimated with increasing precision by the accumulated partial yield from the first four months of lactation.